Molecular Design of Multivalent Glycosides Bearing GlcNAc, (GlcNAc)2 and LacNAc - Analysis of Cross-linking Activities with WGA and ECA Lectins - Ogata, Makoto; Misawa, Yoshinori; Usui, Taichi (IntechOpen, 2011)
None